The Schematic Structure Use of Non-trained and Trained EFL Learner English Major BA Students - Szűcs Ágota (Working Papers in Language Pedagogy, 2018)
Having the appropriate schema plays a crucial role in text comprehension and in the ability to extract relevant pieces of information from a source text. Being able to successfully extract relevant information from a source text is most important in the case of tertiary education students, who are constantly required to solve tasks requiring this skill, for example, taking notes from books, writing summaries, or preparing presentations based on multiple source texts. Therefore, the aim of the present study is to investigate how tertiary education students apply the appropriate formal schema when they have to solve a global summary and a guided summary writing task. The issue raised was investigated by analysing the global and guided summaries written by 12 first year English major BA students before and after receiving training in summary writing. The results suggest that at the beginning of their university studies, first year students completely lack the formal schema required for solving the guided summary task.